2021
DOI: 10.5194/nhess-21-1279-2021
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationary analysis of water level extremes in Latvian waters, Baltic Sea, during 1961–2018

Abstract: Abstract. Analysis and prediction of water level extremes in the eastern Baltic Sea are difficult tasks because of the contribution of various drivers to the water level, the presence of outliers in time series, and possibly non-stationarity of the extremes. Non-stationary modeling of extremes was performed to the block maxima of water level derived from the time series at six locations in the Gulf of Riga and one location in the Baltic proper, Baltic Sea, during 1961–2018. Several parameters of the generalize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…This assumption is unlikely to be completely true. Studies have indicated that sea level extremes have exhibited variations in the Baltic Sea region over different time scales (Johansson et al, 2001;Ribeiro et al, 2014;Marcos and Woodworth, 2017;Kudryavtseva et al, 2021) and that these variations were associated with variations in large scale atmospheric conditions (Samuelsson and Stigebrandt, 1996;Johansson et al, 2001;Ribeiro et al, 2014;Marcos and Woodworth, 2017;Kudryavtseva et al, 2021;Passaro et al, 2021). As with changing mean sea level, future climate is also expected to bring changes in storm surges in the Baltic Sea region (e.g., Vousdoukas et al, 2016Vousdoukas et al, , 2017Vousdoukas et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This assumption is unlikely to be completely true. Studies have indicated that sea level extremes have exhibited variations in the Baltic Sea region over different time scales (Johansson et al, 2001;Ribeiro et al, 2014;Marcos and Woodworth, 2017;Kudryavtseva et al, 2021) and that these variations were associated with variations in large scale atmospheric conditions (Samuelsson and Stigebrandt, 1996;Johansson et al, 2001;Ribeiro et al, 2014;Marcos and Woodworth, 2017;Kudryavtseva et al, 2021;Passaro et al, 2021). As with changing mean sea level, future climate is also expected to bring changes in storm surges in the Baltic Sea region (e.g., Vousdoukas et al, 2016Vousdoukas et al, , 2017Vousdoukas et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…One remedy would be to model temporal dependence directly by allowing (e.g.) linear trends in the GEV parameters (e.g., Ribeiro et al, 2014;Marcos and Woodworth, 2017;Kudryavtseva et al, 2021). Physical covariates, which describe large scale atmospheric circulation conditions around the Baltic Sea region, could also be used to account for interannual-to-decadal scale variations in the annual maximum sea levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Major inflow events are associated with typical volumes in the order of about 100 km 3 , corresponding to a Baltic sea level increase of about 24 cm (Matthäus and Franck, 1992). Typically, such variations have timescales of about 10 d or longer (Soomere and Pindsoo, 2016) while atmospheric variability on shorter timescales primarily leads to a redistribution of water masses within the Baltic Sea basin (Kulikov et al, 2015) or between the Baltic Proper and the Gulf of Riga (Männikus et al, 2019).…”
Section: Variability and Change In Baltic Sea Level Extremesmentioning
confidence: 99%